RISK ASSESSMENT OF ORGAN OF VISION’S NEOPLASMS IN WORKERS EMPLOYED IN THE MODERN OIL INDUSTRY - Kasimov, E.M.; Ibragimova, S.N. (World of Medicine and Biology, 2023)
1,852 employees from 13 enterprises of the oil and gas production profile of the State Oil Company of the Republic of Azerbaijan participated in the study. Clinical examination at the workplace was carried out in 2018–2019 using a mobile clinic operating at the National Center of Ophthalmology named after Acad. Zarifa Aliyeva. The severity of labor was assessed in three groups: class A – optimal, class B – acceptable and class C – harmful working conditions. Of all respondents, 46.5% noted the presence of direct contact with harmful substances during work, 30.5 % – the presence of indirect contact. Pseudo – (49.2 %) and neoplasms (61.6 %) were detected in 33.4 % of workers exposed to exposure. The RR assessment showed that the probability of the development of pseudo – and neoplasms of the visual organ among the studied contingent exposed to exposure is higher than in non–exposed 2.7 (CI=1.95–3.86; χ2=35.87, p
Keywords: neoplasms of the eye; labor severity; relative risk; exposure to harmful substances; oil industry